Comparative Evaluation of Tooth Enamel Surface Microhardness Exposed to Novel Modified Casein Phosphopeptide Amorphous Calcium Phosphate, APF Gel and GC Tooth Mousse - Meeral, P Rahmath; Pandiyan, Indumathy; Arumugham, Meignana (Journal of Dentistry Indonesia, 2024)
Objective: The acidic pH of remineralizing agents is beneficial in etching the enamel to facilitate increased remineralization. This study aims to modify the pH of Casein Phosphopeptide Amorphous Calcium phosphate to acidic and evaluate the enamel surface microhardness exposed to acidified CPP ACPF, acidulated phosphate fluoride (APF gel), and conventional CPP ACPF. Methods: The pH of conventional CPP ACPF (GC Tooth Mousse) is acidified. 24 tooth samples were assigned into three groups receiving as follows: Group 1 (n = 8) acidified CPP ACPF, Group 2 (n = 8) APF gel, and Group 3 (n = 8) CPP ACPF for four minutes. Baseline and post-exposure microhardness values were evaluated using Vicker’s microhardness number. Descriptive and inferential statistics were done. Results: The mean post-surface microhardness was highest in the acidified CPP ACPF group (323 ± 26.0) while lowest in the CPP ACPF group (307 ± 31). The APF gel group had a 312.4±18.6. A one-way ANOVA test between the groups showed statistical significance (p value 0.054), post hoc Tuckey test showed significance between the acidified CPP ACPF and CPP ACPF groups (p value 0.05). Conclusion: Acidified CPP ACPF increased the surface microhardness less than APF gel in a single exposure for four minutes.